A comparative study on initial developments between explosive and nonexplosive cyclones off the East Asian coast in winter - Gao, Xiaoyu; Lu, Ping; Zhang, Shuqin; Hu, Yang; Fu, Gang; Sun, Xiaoyan; Zhang, Qiuyang (Frontiers in Earth Science, 2022)
Explosive cyclones (ECs) pose serious challenges for weather forecasting and significant threats to human life and property. In searching for the key points that make a cyclone go through explosive deepening off the East Asian coast, we present a comparative analysis of ECs and nonexplosive cyclones (or ordinary cyclones; OCs) using 10 years of ERA5 reanalysis data with high temporal and spatial resolutions. Their differences in synoptic backgrounds are shown, and mechanisms of the initial developments are compared quantitatively from the perspective of potential vorticity (PV). Among the identified 135 cyclones, 72 went through explosive growth and 37.5/36.1/20.8/5.6% of these ECs are ranked as weak/medium/strong/super ECs. ECs feature stronger low-level baroclinicity and higher PV than OCs. The decomposition of the local PV tendency shows the dominant role of the PV advection (with a correlation coefficient of 0.8). During the initial development, ECs have an average meridional temperature contrast 4 K larger than OCs within 20 latitudes at the low troposphere in the upstream, due to a stronger cold advection. The upstream colder air increases the horizontal temperature gradient and thus produces steeper isentropic surfaces inclining to the west. Since the PV intrusion is mainly along the isentropic surfaces, the increase in their slope significantly enhances the downward transport of PV from upper air. The importance of the horizontal gradient of potential temperature is further proved by numerical experiments with the Weather Research and Forecast (WRF) model on typical winter ECs. In sensitivity experiments, the low troposphere meridional temperature contrast decreasing by the average difference between ECs and OCs significantly decreases PV and stops the cyclones from explosive deepening. Despite the importance of diabatic processes in the deepening of mid-latitude cyclones emphasized by many studies, this study shows that the PV intrusion dominated by cold air mass is the key cause of winter explosive cyclogenesis in this region.